Ecological impact of the invasive European flounder (Platichthys flesus) on the native European plaice (Pleuronectes platessa) on nursery grounds in Iceland - Henke, Theresa, 1993- (2018)
Verkefnið er lokað til 30.09.2020. In recent years the number of invasive species that have been introduced to new environments has strongly increased, and their further distribution may be favored by both anthropogenic influence and climate change. In 1999, the European flounder (Platichthys flesus), a flatfish species native to central European coasts, was first identified in the southwest of Iceland at the mouth of the Ölfusa river and has since then spread around the whole country. This project investigated the ecological impact of juvenile flounder on juveniles of the native European plaice (Pleuronectes platessa) on nursery grounds. The work focused on two sampling sites representing early and more recent flounder establisment; the fjords Borgarfjörður and Önundarfjörður, respectively. Fish were caught with a beach seine between July and September 2017. Species composition and juvenile size were measured, and stomach content analysis was used to determine niche widhts of each species and overlap in feeding patterns between species. Flounder was present in all collected samples, but both species composition and length distribution of flounder and plaice varied between sites and sampling time. Significant diet overlap between species was observed for some samples, particularly between 1+ flounder and 0+ plaice, which indicates potential for competition between species. Together with observed direct predation of 1+ flounder on 0+ plaice, the presence of the invasive species is likely to have a negative impact on the native plaice population. Differences between the sites of early and more recent invasion could not clearly be linked to the time since invasion. This project highlights that the management of invasive species needs to be improved, especially in locating and restricting pathways of introduction as well as in early detection and rapid response strategies. Á síðustu árum hefur flutningu tegunda út fyrir náttúleg heimkynni aukist mjög. Margvíslegt rask á búsvæðum svo og loftslagsbreytingar auka ...